2007
DOI: 10.1016/j.seppur.2007.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface characteristics of activated carbon on the adsorption of 2-methylisobornel (MIB) and geosmin from natural water

Abstract: Five powdered activated carbons (PACs), including one fruit-based, one wood-based, and three bituminous coal-based, were selected for the investigation of the effects of surface characteristics of activated carbon on the adsorption of 2-methylisobornel (MIB) and geosmin. Characterization of the carbons was performed using nitrogen adsorption, Fourier transform infra-red (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). All the carbons showed a broad absorption band in the 1300-1000 cm −1 region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 37 publications
(55 reference statements)
4
26
1
2
Order By: Relevance
“…PAC's effectiveness as an adsorbent is influenced by various characteristics, including its surface chemistry, pore structure, and particle size. Micropore volume and oxygen content are key properties affecting the equilibrium adsorption capacity of activated carbon (Pendleton et al, 1997, Considine et al, 2001Nowack et al, 2004;Yu et al, 2007;Tennant and Mazyck, 2007). Besides equilibrium capacity, adsorption kinetics is another important aspect of adsorptive removal, and smaller adsorbent particles have faster adsorption kinetics (e.g., Najm et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…PAC's effectiveness as an adsorbent is influenced by various characteristics, including its surface chemistry, pore structure, and particle size. Micropore volume and oxygen content are key properties affecting the equilibrium adsorption capacity of activated carbon (Pendleton et al, 1997, Considine et al, 2001Nowack et al, 2004;Yu et al, 2007;Tennant and Mazyck, 2007). Besides equilibrium capacity, adsorption kinetics is another important aspect of adsorptive removal, and smaller adsorbent particles have faster adsorption kinetics (e.g., Najm et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A broad band at 1300-1000 cm −1 is assigned to C\O stretching in acid, alcohols, phenols, prone, ethers and eaters [20]. The presence of a relatively strong band around 1560 cm −1 can be attributed to the conjugated systems such as diketone, keto-ester and keto-enol structures, carboxylic groups and quinone structure [7,21,22]. This band also appears in all the samples.…”
Section: Characterizations Of Activated Carbon Adsorbentsmentioning
confidence: 85%
“…The presence of a peak for bituminous carbons at~15 Å may indicate a need for smaller micropores as well. Yu et al (2007) found a strong correlation (R 2 ¼ 0.95) for three bituminous carbons for the removal of MIB at pore widths <20 Å . Quinlivan et al (2005) identified a ratio of 1.5Â the critical diameter of an adsorbate (in this case~11.2 Å for MIB as calculated from Table 2) as necessary for adsorption.…”
Section: Correlations Between Idcs Rsscts and Pvdsmentioning
confidence: 91%
“…Mesopores provide transport for smaller molecules (MIB) as well as storage for larger molecules such as NOM (Hsieh et al, 2000;Newcombe et al, 2002). Several authors have discussed the effects of surface chemistry and pore volume distributions on the sorption of MIB and similar trace compounds (Karanfil et al, 1999;Redding et al, 2009;Snyder et al, 2007;Tennant et al, 2007;Mackenzie et al, 2005;Yu et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation